2005
DOI: 10.1111/j.1523-1755.2005.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal membrane function in functionally anuric patients treated with APD: Data from EAPOS on the effects of glucose and icodextrin prescription

Abstract: Anuric automated peritoneal dialysis (APD) patients experience significant detrimental changes in membrane function over a relatively short time period. Glucose appears to enhance these changes independent of residual renal function. Icodextrin use in these circumstances is associated with less deterioration in membrane function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 22 publications
2
121
0
3
Order By: Relevance
“…Although spontaneous bacterial peritonitis cannot be ruled out, the cell counts in each of these rats was low (mean 71 cells/mm 3 ) and the positive cultures were likely the result of accidental bowel perforation at the intraperitoneal injection, just before the transport experiments. A relatively low cell count was also observed for nearly half of the rats that received a needle injection (NI) and whose culture was positive.…”
Section: Bacterial Cultures and Cell Counts After Injection Periodmentioning
confidence: 94%
See 1 more Smart Citation
“…Although spontaneous bacterial peritonitis cannot be ruled out, the cell counts in each of these rats was low (mean 71 cells/mm 3 ) and the positive cultures were likely the result of accidental bowel perforation at the intraperitoneal injection, just before the transport experiments. A relatively low cell count was also observed for nearly half of the rats that received a needle injection (NI) and whose culture was positive.…”
Section: Bacterial Cultures and Cell Counts After Injection Periodmentioning
confidence: 94%
“…2 Exposure of patients to glucose-based dialysis solutions resulted in significant functional changes in transperitoneal transport in a 2-yr study of patients who were treated with automated PD. 3 Studies in animal models parallel these changes and have demonstrated benefit of solutions that are thought to be more biocompatible. 4 -6 Studies in our laboratory using an animal model with a subcutaneous injection port connected to a silicone catheter tunneled to the cavity demonstrated angiogenesis and thickening of the perito-neum after 8 wk of daily exposure to sterile solutions.…”
mentioning
confidence: 99%
“…Impaired ultrafiltration severe enough to require cessation of PD occurs in about 10% of cases [22], which then requires referral to alternative renalreplacement therapy. Long-term PD for more than 2 years, repeated peritonitis, exposure to glucose in PD solution, diabetes, and beta-blockers contribute to these phenomena [23,24]. Therefore, detecting time-dependent functional and structural changes of the PM is important to sustain PM function in the long term, and to plan any referral to alternative renal-replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Icodextrin use may be associated with preservation of PM function. In EAPOS (55), longitudinal changes in membrane function were least apparent in the patients using icodextrin from the start of PD. Patients using icodextrin had no change in UF capacity whereas patients using 2.27% or 3.86% dextrose had a significant decrease in UF capacity at 2 years.…”
Section: Dialysis Fluids and Pm Integritymentioning
confidence: 92%